Holistic wild bee management in urban spaces - Weissmann, Julie A.; Rader, Sandra; Ritz, Rasmus; Walldorf, Iris R. M.; Probst, Juliane; Szydlik, Kristin R.; Schaefer, Hanno (Frontiers in Sustainable Cities, 2023)
Projects promoting bees in urban areas are initiated in cities around the world but evidence-based conservation concepts at a city-wide scale are scarce. We developed a holistic approach for assessment of bee and flowering plant diversity in a medium-sized city. In addition to standard mapping approaches in bee hotspots, we initiated citizen science projects for participative urban bee research to be able to collect comprehensive bee data across the entire city. We identified 22 hotspots of bee diversity, analyzed connectivity between those hotspots and evaluated the impact of flower patches planted in collaboration with the municipal gardens department as stepping stones for oligolectic bee species throughout the city. Participation by urban citizens in bee identification trainings was high (c. 630 persons) but their subsequent contribution through observation reports was relatively low (1165 records by 140 observers). However, we identified a total of 139 bee taxa, seven of them only discovered by citizen scientists. Total species richness was higher in extensively managed orchards than in semi-natural and wasteland areas. Half of the stepping stone flower patches were occupied by the target oligolectic bee species in the year of planting. After three years, all but two species could be confirmed. We suggest a 5-step concept for bee management in cities: 1) identification of bee hotspots combined with standardized surveys, especially of rare species; 2) training of citizen scientists at two different levels for comprehensive surveys in all parts of the city: (a) half-day introductions to wild bee diversity, ecology and conservation in order to create more awareness and (b) two-weeks workshops for in-depth training of a small number of dedicated citizen scientists; 3) extensive management of existing habitats and special conservation programs for very rare species; 4) creation of high-value habitats which take into account the varied resource needs of bees within flight ranges of only a few hundred meters; 5) creation of stepping stone habitats as floral and nesting resources, integrating educative and participative aspects.